Hub Communication Platform (HCP) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
HCP is an information sharing and communication platform for linking farmers, agri-service businesses, the public-private sector, the scientific community and outside CSISA stakeholders. The vision of the HCP is to serve as a multi-directional, location based, information sharing system in support of accelerating the impact of agricultural investments across the region.